Antecedent Of Halal Food Purchasing Decision: A Theory Of Planned Behavior (TPB) Approach - Hasyim, Fuad; Purnasari, Nurwulan (Ekonomi Syariah IAIN Kudus, 2021)
The purpose of this study is to investigate the factors that influence Indonesian customers in purchasing decisions for halal food. The approach taken uses the theory of planned behavior (TPB) because this theory emphasizes the aspects of individual behavior in making purchase decisions. Data obtained from distributing e-questionnaires with random sampling technique. The data is processed using structural equation modeling (SEM). The results show that all TPB constructs have a significant influence on the purchase of halal food by Indonesian customers. This research adds to and expands our knowledge of the halal food purchasing decision, as well as identifying the rationales for halal food purchases. From a managerial standpoint, the findings support investment decisions and relate to Indonesia's growth as a halal hub (supply chain) that addresses and considers the concerns and needs of businesses and Indonesian government agencies..